Challenges and Support Strategies for Grade 11 Afrikaans First Additional Language Learners - Schlebusch, Gawie; Hinckemann, Alicia (Universitas Muhammadiyah Yogyakarta, 2025)
Background: The article explores the challenges and support strategies for Grade 11 Afrikaans First Additional Language (FAL) learners. The Curriculum and Assessment Policy Statement (CAPS) outlines a detailed framework for teaching all subjects in South Africa's basic education system. According to CAPS, learners in the Further Education and Training (FET) phase must study at least two official languages from the South African constitution. One of these must be the learner’s home language (HL), while another official language can be taught as a first additional language. CAPS also mandates that from Grade 1, learners begin learning a second language, referred to as FAL. Objective: This qualitative study aims to identify the challenges learners face in the Afrikaans FAL classroom, focusing on language skills and examination papers. It also seeks to explore specific areas of difficulty and offer insights to inform teaching practices and support in the classroom. Methods: A qualitative phenomenological approach was employed, with data collected through individual and focus group interviews. Semi-structured interviews were conducted with Grade 11 Afrikaans FAL teachers and learners, using purposeful sampling for participant selection. Findings: The findings revealed that learners faced significant challenges in mastering Afrikaans, especially in reading, writing, and speaking. These difficulties were influenced by negative transfer from their home language, limited vocabulary, and lack of exposure to Afrikaans. Conclusion: Negative attitudes towards the language further reduced motivation and engagement, while the support provided did not adequately address learners’ needs, highlighting gaps in both classroom support and resources from the Department of Basic Education (DBE).